2013
DOI: 10.1242/dev.096099
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal-B and caudal inhibit the formation of specific neuroblasts in the Drosophila tail region

Abstract: The central nervous system of Drosophila melanogaster consists of fused segmental units (neuromeres), each generated by a characteristic number of neural stem cells (neuroblasts). In the embryo, thoracic and anterior abdominal neuromeres are almost equally sized and formed by repetitive sets of neuroblasts, whereas the terminal abdominal neuromeres are generated by significantly smaller populations of progenitor cells. Here we investigated the role of the Hox gene Abdominal-B in shaping the terminal neuromeres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 116 publications
(130 reference statements)
0
28
0
Order By: Relevance
“…The homeobox genes of the Antennapedia and bithorax complexes specify the anterior/posterior segmental identity of the Drosophila embryo. 11,34,37,[39][40][41] A role for a pulse of abdA expression to activate the death of postembryonic NBs has been previously demonstrated, 11 as has the involvement of abdA in embryonic NB fate. 35 Here, we show that AbdA regulates NB death in the embryo, acting upstream of Enh1 to turn on rpr and grim transcription specifically in abdominal NBs.…”
Section: Discussionmentioning
confidence: 94%
“…The homeobox genes of the Antennapedia and bithorax complexes specify the anterior/posterior segmental identity of the Drosophila embryo. 11,34,37,[39][40][41] A role for a pulse of abdA expression to activate the death of postembryonic NBs has been previously demonstrated, 11 as has the involvement of abdA in embryonic NB fate. 35 Here, we show that AbdA regulates NB death in the embryo, acting upstream of Enh1 to turn on rpr and grim transcription specifically in abdominal NBs.…”
Section: Discussionmentioning
confidence: 94%
“…The VNC is formed from the ventral part of the neuroectoderm by highly conserved anterior-posterior and dorsal-ventral patterning of the embryo (Skeath 1999;Skeath and Thor 2003). The VNC can be subdivided into three thoracic and 10 abdominal segments (Birkholz et al 2013). During early embryogenesis 30 progenitors, denoted neuroblasts (NBs), are born in each hemi-segment (Bossing et al 1996;Schmidt et al 1997;Schmid et al 1999).…”
mentioning
confidence: 99%
“…In addition to their early role in shaping large cellular territories, Hox genes influence the activities of individual cells, controlling processes in the CNS such as programmed cell death, [12][13][14][15] proliferation, 9,16,17 and cell specification. 13,15,[17][18][19][20][21] (Table 1) …”
Section: Neurogenesis In Drosophilamentioning
confidence: 99%
“…For example, Birkholz et al 15 have shown that Abd-B inhibits the formation of a specific set of NBs in the most posterior abdominal segments. Specifically, they found that there were more neuroblasts in parasegment 15 (i.e., the posterior half of abdominal segment 9 and anterior half of abdominal segment 10) in Abd-B mutant embryos than in the wild-type, 1 of these extra progenitors being NB7-3 and its lineage.…”
Section: How Do Hox Genes Provide Diversity In the Cns?mentioning
confidence: 99%
See 1 more Smart Citation